Antioxidant phytochemicals and curcuminodes content in different genotypes of turmeric (Curcuma longa) - SANWAL, S K; DEKA, B C; KOZAK, MARCIN (The Indian Journal of Agricultural Sciences, 2026)
Fresh rhizomes of 21 genotypes of turmeric, including commercial cultivars and experimental genotypes, wereassayed for curcuminodes content and antioxidant activity for two consecutive years. Curcumin was the most abundantcurcuminode in all the genotypes, which occurred at concentrations ranging from 1.3 % to 4.5 % (with mean of 2.8 % ± standard deviation of 0.45 %), whereas dimethoxycurcumin and bismethoxycurcumin occurred in lower concentration: dimethoxycurcumin ranged from 0.48 to 2.40 % (1.50 ± 0.12 %) while bismethoxycurcumin from 0.43 to 3.70 % (1.37 ± 0.11%). Genotype RCT-2 had the highest contents of curcuminodes and the highest antioxidant activity. Correlation of total phenolics with different antioxidant assay was linear and strong. Curcumin and demethoxycurcumin also had a strong positive correlation with both the antioxidant assay.